Kajian Kegiatan Perikanan Masyarakat Nelayan Tradisional Kota Sorong dan Peluang Pengembanganya - Endang Gunaisah; Amir M Suruwaky; Yuniar Endri Priharanto (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2012)
Sorong regency has abundance potency of coastal area resource, however it has not been fully optimized to prosperity of coastal community, thereby needed to identify about it. The studi done to identify the socio-economic baseline of coastal communities ,describing the human condition as seen from the level of education and employmen in fishing and no fishing and identify factors that affect revenue factors. Method of data collection with quantitative and qualitative. Instruments used were questioner while the analysis of data processed by a computerizen office excel. The highest fishery production in Sorong at 2009 it was 74,37% and demersal 9,19%. The traditional fisheries is recommended fishing by bubu kepiting, jaring insang udang, jaring insang hanyut, jaring insang dasar, pancing rangkai dan rawai, whereas seaweed aquaculture and Keramba jaring apung are the alternative for fisheries aquaculture.